Cor do solo na caracterização de áreas específicas de manejo para cultura do café - Carmo, Danilo Almeida Baldo do [UNESP] (2014)
The advance in the knowledge of the soil attributes enthused satisfactorily the end result of agricultural activities, both in productive potential, as well as the aggregated values to final product. Thus, objective of this study was to evaluate the color of the soil obtained by diffuse reflectance spectroscopy - VIS-NIR, for the mapping of specific areas of management in coffee culture. The experiment was carried out in an area of 39 ha with cultivation of coffee, located in the city of Chichester, south west of the State of Sao Paulo. The area was on the cultivation of coffee variety Coffea arabic L. (IAC Yellow Catuai-62 variety). For the installation of the experiment, plants were used with 7 years of age, in a planting spacing of 3.5 x 0.50 m. The sampling points for analysis of soil and plant analyzes were carried out with regular interval, using between points 45 m, which totaled 173 points in total area. The samples of soil were taken from a depth of 0.0 - 0.20 m. Of this collected soil, was removed from 0.5 g, which was crushed and dried in air, thus determining the values of diffuse reflectance in the range of 380 to 780 nm, obtaining values of hue, value and chroma that promoted together the result of redness index. The values of each attribute were correlated to variables productive and qualitative of the plant. Moreover, the results showed the existence of correlations with attributes of the plant, indicating that the constituents of color can be used as predictors of the analyzed variables